PEMILIHAN ANTI NYAMUK DITINJAU DARI TINGKAT PENDIDIKAN, PENDAPATAN DAN PRILAKU SERTA KELUHAN KESEHATAN PADA KELUARGA DI KELURAHAN ASAM KUMBANG KECAMATAN MEDAN SELAYANG TAHUN 2015 - siti hardinisah; irnawati marsaulina; devi nuraini santi (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Various types of anti-mosquito have been circulating in the market such as the burn anti-mosquito, electrical anti-mosquito, anti-mosquito lotion and anti-mosquito spray. Community use anti-mosquito due to more practical, inexpensive and readily available. People use the anti-mosquito to protect themselves from mosquito bites but if it is used too often, it will cause mosquito resistent and would interfere with human health. The purpose of this study is to determine the type of anti-mosquito which is the most preferred by the communities includes characteristics, behaviors and perceived health complaints in Sub Asam Kumbang family. This research is a descriptive study with cross sectional design. The population in this study were all housewives in the village of Medan Selayang Asam Kumbang districts. The total sample of 98 respondents with purposive sampling method. The results based on the selection of the type of anti-mosquito spray with the highest number of 44 persons (44.9%), type of lotion amounted to as many as 32 people (32.6%), type of fuel amounted to 19 people (19.4%) and the type of electrical amounted to 19 people (19.4%). Respondents who felt health complaints as many as 16 people (16.3%) such as cough, nausea, difficulty in breathing, headaches and itchy skin. From the research, it is known that people use the anti-mosquito spray the most so it is advised to use personal protective equipment such as gloves and masks for decreasing the risk of poisoning and it is recommended to read the procedures for the use of (labeled) anti-mosquito before using it and it is also recommended not to use anti-mosquito too often to prevent mosquito resistent. Keywords: anti-mosquito, selection, health complaints